How 9 Cheenta students ranked in top 100 in ISI and CMI Entrances?

# Understand the problem

[/et_pb_text][et_pb_text _builder_version="3.22.4" text_font="Raleway||||||||" background_color="#f4f4f4" box_shadow_style="preset2" custom_margin="10px||10px" custom_padding="10px|20px|10px|20px"]Find all polynomials with real coefficients $P(x)$ such that $P(x^2+x+1)$ divides $P(x^3-1)$.

[/et_pb_text][et_pb_tabs active_tab_background_color="#0c71c3" inactive_tab_background_color="#000000" _builder_version="3.23.3" tab_text_color="#ffffff" tab_font="||||||||" background_color="#ffffff"][et_pb_tab title="Hint 0" _builder_version="3.22.4"]Do you really need a hint? Try it first!

[/et_pb_tab][et_pb_tab title="Hint 1" _builder_version="3.23.3"]Show that, given a zero of $P$, it is possible to find another zero.[/et_pb_tab][et_pb_tab title="Hint 2" _builder_version="3.23.3"]Whenever such a property holds (as in hint 1), it is a good idea to use the extremal principle (that is, looking at extremal elements).[/et_pb_tab][et_pb_tab title="Hint 3" _builder_version="3.23.3"]Among all (possibly complex) zeros of $P$, consider the one with the maximum absolute value. Show that, for most choices of $P$, it is possible to construct another zero with larger absolute value. As that is absurd, a large number of options for $P$ are eliminated.

[/et_pb_tab][et_pb_tab title="Hint 4" _builder_version="3.23.3"]

As $P(x^3-1)$ is divisible by $P(x^2+x+1)$, there exists a polynomial $Q(x)$ such that $P(x^2+x+1)Q(x)=P(x^3-1)$. Let $z$ be a zero of $P$. If $x^2+x+1=z$ then $x=\frac{-1\pm\sqrt{1+4(z-1)}}{2}$, i.e. $x^3-1= (x-1)(x^2+x+1)=z\left(\frac{-3\pm\sqrt{4z-3}}{2}\right)$. The given equation means that $z\left(\frac{-3\pm\sqrt{4z-3}}{2}\right)$ are also zeroes of $P$. Claim One of the two numbers $\left|\frac{-3\pm\sqrt{4z-3}}{2}\right|$ is greater than 1.   Proof Suppose that they are both $\le 1$. Then we have    $2\ge |-3+\sqrt{4z-3}|$   $2\ge |-3-\sqrt{4z-3}|$ Adding these two inequalities we get $4\ge |-3+\sqrt{4z-3}|+|-3-\sqrt{4z-3}|\ge |(-3+\sqrt{4z-3})+(-3-\sqrt{4z-3})|=6$ which is absurd. Hence at least one of them has to be greater than 1.     The claim means that, if $z$ is non-zero, then at least one of the two zeroes $z\left(\frac{-3\pm\sqrt{4z-3}}{2}\right)$  has absolute value greater than $|z|$.

Now let $z=z_0$, the zero of $P$ with the largest absolute value. The procedure mentioned above can be used to construct a zero with absolute value bigger than $|z_0|$, which is absurd unless $z_0=0$. As $z_0$ is largest among the zeroes in absolute value, this means that $P$ does not have any nontrivial zeroes. Hence $P(x)=ax^n$ for some $a\in\mathbb{R}$ and $n\in\mathbb{N}$.

# Similar Problems

[/et_pb_text][et_pb_post_slider include_categories="9" _builder_version="3.22.4"][/et_pb_post_slider][et_pb_divider _builder_version="3.22.4" background_color="#0c71c3"][/et_pb_divider][/et_pb_column][/et_pb_row][/et_pb_section]